Preguntas paradigmáticas sobre el teatro hispanocaribeño isleño y la diáspora - Fiet, Lowell (Latin American Theatre Review, 2004)
The need to ask the question "What is Hispanic Caribbean Theatre?" retains its fundamental agency as long as attempts to forge answers are tempered by, first, the integration of the dramatic expression and performance forms of the Latina/o Caribbean diaspora in the US and, second, an appraisal of the, at once, homogenizing and disintegrating impact on the island societies and cultures of geopolitical Caribbean of economic and electronic media globalization or "Americanization." A brief examination of Anna in the Tropics, the 2003 Pulitzer Prize winning play by Cuban American author Nilo Cruz, leads to queries of what makes a play "Caribbean-American," "Cuban-American," or simply "American," in its use of the conventions and language of the mainstream US theatre. The conclusion proposes a redefinition of the relation between the theatre and performance forms the island or geopolitical Caribbean and the Latina/o diaspora as aesthetic/critical continuity rather than as extension or separation. (LF, in Spanish)